A Retrospective Study of Pyometra in Canines - Pitroda, Manisha; Kumar Singh, Ashwani; Singh, Rajsukhbir; Kumar, Ajeet; Honparkhe, Mrigank; Singh Randhawa, Swaran (The Indian Journal of Animal Reproduction, 2025)
The present study has been undertaken to investigate the prevalence of pyometra and document variation in breed and age of dogs vis-à-vis pyometra through a retrospective study. Data pertaining to all dogs presented for treatment of pyometra between 2016 and 2021 were gathered from electronic records maintained at University Veterinary Hospital. During the study period, a total of 4502 dog outpatient caseloads having reproductive problems were presented in the hospital, out of which 336 dogs suffered from pyometra, resulting in a prevalence of 7.5 percent. Within breed, the prevalence was higher in Saint Bernard (71.4%), Tibettan Mastiff (54.5%) and Dalmation (43.7%) and lower in Golden Retriver (5.0%) and German Shephard (3.4%). The age at presentation was lower in Tibettan Mastiff (1.5±0.5 years) and Pug (2.9±0.4 years) and higher in Dalmation (10.5±0.5 years) and Pomeranian (7.4±1.4 years) breeds of dogs. Neutrophilia (95.8%), anemia (87.7%), leukocytosis with left shift and increased levels of alkaline phosphatase (96.7%), blood urea nitrogen (75%) and creatinine (84.2%) appeared to be characteristic hematological and biochemical findings, respectively in pyometra. Maximum caseloads were presented during spring (32.7%), followed by autumn (20.5%), summer (16.9%), monsoon (16.7%) and winter (13.0%). The most common complication associated with pyometra included kidney malfunction (84.2%). Ovariohysterectomy is the treatment of choice in most caseloads (86.6%). The overall incidence of mortality due to pyometra was 12.2 percent. Vaginal swab bacteriological examination revealed the predominance of Escherichia coli (66.7%). These observations serve to highlight the importance of public awareness regarding pyometra in canines.